Differential subcompartmentation of terminal glycosylation in the Golgi apparatus of intestinal absorptive and goblet cells - Roth, J; Taatjes, D J; Weinstein, J; Paulson, J C; Greenwell, P; Watkins, W M (The Journal of biological chemistry, 1986)
Two terminal glycosyltransferases, a sialyltransferase and the blood group A alpha 1,3 N-acetylgalactosaminyltransferase, were found to exhibit differential subcompartmentation in the Golgi apparatus of intestinal goblet and absorptive cells. As expected from their role in terminal glycosylation, the two glycosyltransferases and their products, sialic acid residues and blood group A substance, were localized in the trans cisternae of the Golgi apparatus of goblet cells. In contrast, however, they were found throughout the Golgi apparatus stack of adjacent absorptive cells, with the exception of the fenestrated first cis cisterna. The results are in contrast to the general view that enzymes in the glycosylation pathway are arranged in a cis to trans gradient across the Golgi apparatus and that such polarized distributions may instead be cell type-specific.